The relationship between internal and external factors on attitude towards acceptance of change among Officers of Malaysian Government Sectors - Mohamad Shuhaimi, Suzalina; Ma’rof, Aini Azeqa; Kunasekaran, Puvaneswaran; Dahamat Azam, Mohamad Naqiuddin (Human Resource Management Academic Research Society, 2024)
This study investigates the influence of psychological readiness for change, perceived organizational support, change communication quality, and perceived job security on attitudes toward acceptance of organizational change among officers in the Malaysian government sector. A quantitative approach was employed with a sample of 394 participants, utilizing Pearson correlation and multiple regression analyses to explore the relationships between these variables. The findings revealed that perceived organizational support was the strongest predictor of positive attitudes toward change, followed by psychological readiness, change communication quality, and perceived job security. The results highlight the critical role of organizational support and psychological readiness in fostering positive attitudes toward change, with effective communication further enhancing acceptance. Although perceived job security was a significant factor, its influence was slightly weaker. These findings suggest that organizations should focus on providing robust support systems, clear communication strategies, and building psychological readiness to facilitate smoother change processes. Policymakers and organizational leaders are encouraged to implement strategies that reinforce these factors to ensure successful change management within government sectors.